Analysis of Work-Life Balance and Job Satisfaction on Employee Performance at Bank Mandiri Kupang Branch Office - Shally Urfa Ramadhania; Gendut Sukarno (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the effect of work-life balance variables and job satisfaction on employee performance at Bank Mandiri Kupang Branch Office. The approach uses a quantitative approach. The data was collected from a questionnaire, where the score was calculated based on a measurement scale between numbers 1 to 5 on research variables. The method used to retrieve the data is non-probability sampling, where the technique is in the form of saturated sampling, namely all employees of Bank Mandiri Kupang Branch Office with a total of 35 people. Data were analyzed using PLS (Partial Least Square). The results show that work-life balance has a significant positive effect on employee performance. Furthermore, resulted that employee performance was positively and significantly influenced by job satisfaction.